Use Fiber-Reinforced Polymer Bars in Concrete Structures Subject to Dynamic Loads - Mamin, A. N.; Khlebnikov, S. K. (Železobetonnye konstrukcii, 2025)
The article examines the properties of fiber-reinforced polymer bars (FRP bars) and its use in concrete structures. With its high tensile strength, low density, and corrosion resistance, FRP bars presents a promising alternative to traditional steel reinforcement, particularly in aggressive environments. However, its widespread application is limited by several factors, including the insufficient study of FRP bars behavior and the performance of concrete structures reinforced with it under dynamic loads. The article describes FRP bars as a heterogeneous anisotropic material composed of continuous reinforcing fibers and a polymer matrix. It provides a classification of FRP bars, analyzes its physical and mechanical properties under static, long-term, and dynamic loading conditions, and discusses calculation methods for reinforced concrete structures incorporating FRP bars. A deformation diagram for static tension and compression, obtained from experimental tests, is presented. Under short-term static loading, FRP bars deforms elastically without forming plastic zones. However, under prolonged exposure, polymer creep leads to a reduction in FRP bars’ strength characteristics. The behavior of fiber-reinforced polymer bars under dynamic loads remains underexplored, although some studies indicate the presence of a dynamic hardening effect under short-term dynamic loading. Additional research is needed to determine the influence of strain rate on FRP bars properties. The study proposes recommendations for modeling loading conditions in tests of flexural elements, considering their deformation behavior under cyclic dynamic loads. The analysis of the obtained results highlights the need for further research on FRP bars under cyclic dynamic loading, which would expand the scope of fiber-reinforced polymer bars applications in construction.